Rancang Bangun Alat Ukur Tahanan Tanah (Earth Meter) Digital - Hendra Firdaus (Jurnal Soshum Insentif, 2018)
Ground resistance is required for protection of electrical installations. The size of the earthing resistance value has an effect on the rapidly discharging of electrical energy. The value of grounding resistance that meets the requirements of an Electrical Installation has been determined and set by PUIL (General Requirements for Electrical Installation) 2000. Methods are performed based on circuit-designed trials and measurement results. The design of this digital ground resistance measurement is not separated from the basic circuit of current and voltage measurement, the achievement of the measurement of ground resistance is generated from the measurement of voltage and current (V / I). The test results of the tool can be seen that the measuring tool of digital grounding resistance that is designed to build this has a precision and accuracy is good enough that the average percentage error of 6.29%. This measuring instrument uses two voltage sources that is the voltage for the measuring instrument and the reference voltage that is supplied to each electrode. In the use of this measuring device must be careful because the reference voltage is high enough that it can create a shock voltage on the electrode if not installed properly.